Korelasi aktivitas fisik dan asupan kalium terhadap tekanan darah lansia - Wahyuni, Devi; Widhi, Anisa Sekar (Jurnal Gizi Klinik Indonesia, 2024)
Correlation between physical activity and potassium intake with blood pressure in the elderlyBackground: Setabelan Health Center, Banjarsari District, Surakarta City, recorded 59% higher cases of hypertension than other health centers (average below 45%). The high cases of hypertension in the elderly are influenced by lifestyle and food consumption patterns. Objective: This study aims to determine the correlation between physical activity and potassium intake with blood pressure in the elderly in the Setabelan Health Center work area. Methods: Observational study with a cross-sectional approach on 85 older adults. This study used the Global Physical Activity Questionnaire (GPAQ) questionnaire to measure physical activity and the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) questionnaire for potassium intake data. Data analysis using the Chi-Square test. Results: The majority of respondents had moderate physical activity (62%), experienced potassium deficiency (96%), abnormal systolic blood pressure (66%), and normal diastolic blood pressure (69%). Physical exercise correlated with systolic blood pressure (p=0.014) and diastolic blood pressure (p=0.024). Likewise, potassium consumption with systolic blood pressure (p=0.047) and diastolic (p=0.007) in the elderly. Conclusions: Physical activity and potassium intake are correlated with blood pressure in the elderly.